PENGARUH ENVIRONMENTAL PERFORMANCE TERHADAP ECONOMIC PERFORMANCE - Titisari, Kartika Hendra; Alviana, Khara (Manajemen Bisnis Syariah, 2012)
This study examined the relationship of environmental performance against the economic performance of companies in Indonesia. Economic  performance measured by ROA (return on assets). Environmental performance is measured by rating the environmental performance of companies or PROPER provided by Bapedal / Ministry of Environment. This study proves the hypothesis of unity that collectively - as there is significant influence between environmental performancet (PROPERt), total assetsst, industry sektort, and between ISO 14001t of economic performancet (ROAt), but the t test to prove there is positive but not significant between (a) environmental performancet (PROPERt) on economic performancet (ROAt), total assetsst of economic performancet (ROAt), (b) the influence sektor industryt of economic performancet (ROAt), and (c) ISO 14001t of economic performancet (ROAt). In the second hypothesis together there is no significant effect between environmental performancet (PROPERt), total assetsst, industry sektort, and between ISO 14001t  of economic performancet+1 (ROAt+1), and the t test that there is positive but not significant between (a) environmental performancet (PROPERt) on economic performancet+1 (ROAt+1), (b) total assetsst of economic performancet+1 (ROAt+1), and (c) ISO 14001t of economic performancet+1 (ROAt+1), however there are negative and not significant between the influence sektor industryt of economic performancet+1 (ROA t+1). This study also proved that rating, which is provided by the Indonesian government, it is quite reliable as a measure of corporate environmental performance, because compliance with international certification in the field of environment,ISO14001. Keywords: economic performance, environmental performance, total assets, industry sectors, ISO 14001.